Enrichment of skeletal stem cells from human bone marrow using spherical nucleic acids - Xavier, M; Kyriazi, M-E; Lanham, S; Alexaki, K; Matthews, E; El-Sagheer, AH; Brown, T; Kanaras, AG; Oreffo, ROC (American Chemical Society, 2021)
Human bone marrow (BM)-derived stromal cells contain a population of skeletal stem cells (SSCs), with the capacity to differentiate along the osteogenic, adipogenic, and chondrogenic lineages, enabling their application to clinical therapies. However, current methods to isolate and enrich SSCs from human tissues remain, at best, challenging in the absence of a specific SSC marker. Unfortunately, none of the current proposed markers alone can isolate a homogeneous cell population with the ability to form bone, cartilage, and adipose tissue in humans. Here, we have designed DNA-gold nanoparticles able to identify and sort SSCs displaying specific mRNA signatures. The current approach demonstrates the significant enrichment attained in the isolation of SSCs, with potential therein to enhance our understanding of bone cell biology and translational applications.